Pathways in environmental sociology: Expertise, climate science and science denial (Sociologisk Forskning, 2026)
The article examines theory choices and conceptions of knowledge within the field of environmental sociology against the backdrop of recent electoral successes of climate- and science-denying right-wing populist parties. The new political situation calls for a critical review of epistemological positions within the field. A central question concerns how findings from climate science should be integrated into sociological studies of the climate crisis – either as a point of departure or as an object of problematization. Another key tension lies between the risk that anti-democratic expert regimes may legitimize themselves by invoking a climate emergency, and the opposing risk that the public is misled and kept ignorant of the causes and consequences of climate change. How one positions oneself on these issues largely depends on whether expertise is understood as grounded in substantive knowledge of external realities or as a relational, socially attributed property. Positions within environmental sociology tend to be divided between a natural-scientific and/or political–economic orientation and an STS-inspired orientation. Through a close reading of the work of Rolf Lidskog and Göran Sundqvist – two prominent representatives of the latter approach – the article examines epistemological assumptions and lines of conflict within environmental sociology. The aim of the article is to clarify the crossroads facing environmental sociology in a time of climate emergency, crisis of trust in expertise, and authoritarian populism.
Keywords: post-truth; STS; expert knowledge; climate denial; environmental sociology